2018
DOI: 10.1002/bjs.10644
|View full text |Cite
|
Sign up to set email alerts
|

Optimal extent of completion lymphadenectomy for patients with melanoma and a positive sentinel node in the groin

Abstract: BackgroundThe optimal extent of groin completion lymph node dissection (CLND) (inguinal or ilioinguinal dissection) in patients with melanoma is controversial. The aim of this study was to evaluate whether the extent of groin CLND after a positive sentinel node biopsy (SNB) is associated with improved outcome.MethodsData from all sentinel node‐positive patients who underwent groin CLND at four tertiary melanoma referral centres were retrieved retrospectively. Baseline patient and tumour characteristics were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
5
2
Order By: Relevance
“…First, it is worth highlighting the methodological problem that Kaplan–Meier survival curves lose reliability with an N below 30. Nevertheless, other authors found better survival from OIL to LIIL; however, unlike our results, statistical significance was not demonstrated [ 16 , 18 ]. Contrary to the findings of Rossi et al [ 15 ], the greater number of resected nodes has not been associated with a better prognosis of LIIL ( Figure 3 ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…First, it is worth highlighting the methodological problem that Kaplan–Meier survival curves lose reliability with an N below 30. Nevertheless, other authors found better survival from OIL to LIIL; however, unlike our results, statistical significance was not demonstrated [ 16 , 18 ]. Contrary to the findings of Rossi et al [ 15 ], the greater number of resected nodes has not been associated with a better prognosis of LIIL ( Figure 3 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our local recurrence rate was higher than in the literature, which varies from one digit to 35% [ 6 , 16 , 17 ]. The fact that 60% of the patients in our series had macroscopic inguinal involvement, with a LN ratio category B (10–25%) and more than 40% of T4s, reflect a locally advanced melanoma case series, with an expected worse local recurrence rate.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…In patients with evidence of only inguinal disease, the survival benefit of performing an ilioinguinal dissection over an inguinal dissection alone is unknown. High-level evidence regarding which operation offers most oncological benefit does not yet exist, and is currently being investigated as part of the Evaluation of Groin Lymphadenectomy Extent for Metastatic Melanoma (EAGLE-FM) (NCT02166788) RCT 4 . Under current National Institute for Health and Care Excellence guidance, patients with melanoma AJCC stage IIC (melanoma larger than 4 mm with ulceration) or above (stage III (any lymph node involvement) and stage IV (any metastatic disease)) should have staging CT of the chest, abdomen and pelvis, and MRI of the brain.…”
Section: Introductionmentioning
confidence: 99%